2022
DOI: 10.1021/acsami.1c19790
|View full text |Cite
|
Sign up to set email alerts
|

Tin Oxide Electron Transport Layers for Air-/Solution-Processed Conventional Organic Solar Cells

Abstract: Commercialization of organic solar cells (OSC) is imminent. Interlayers between the photoactive film and the electrodes are critical for high device efficiency and stability. Here, the applicability of SnO 2 nanoparticles (SnO 2 NPs) as the electron transport layer (ETL) in conventional OSCs is evaluated. A commercial SnO 2 NPs solution in butanol is mixed with ethanol (EtOH) as a processing co-solvent to improve film formation for spin and slot-die coating deposition procedures. When processed with 200% v/v E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…For reference, Welch et al reported a V oc of 0.52 V and PCE of 3.4% when fabricating the PTQ10:IDIC binary cells with a conventional architecture and measuring in air. 43 In addition, we measured binary blend solar cells of PTQ10:IDID and IDID:PC 61 BM as controls and the results are shown in Table S2. IDID:PC 61 BM showed no measurable photovoltaic effect, possibly due to the inability to generate a uniform film.…”
mentioning
confidence: 99%
“…For reference, Welch et al reported a V oc of 0.52 V and PCE of 3.4% when fabricating the PTQ10:IDIC binary cells with a conventional architecture and measuring in air. 43 In addition, we measured binary blend solar cells of PTQ10:IDID and IDID:PC 61 BM as controls and the results are shown in Table S2. IDID:PC 61 BM showed no measurable photovoltaic effect, possibly due to the inability to generate a uniform film.…”
mentioning
confidence: 99%
“…It is noteworthy that the efficiency of the devices remained at 12% with a 530 nm thick blade-coated SnO 2 layer. Recently, Hoff et al successfully deposited SnO 2 nanoparticles (NPs) on top of the active layers in air by slot-die coating 133 . Ethanol was added to a commercial SnO 2 solution to improve the film quality.…”
Section: Solution-processed Interface Layersmentioning
confidence: 99%
“…[8,13] For large-area applications that are compatible with roll-to-roll fabrication techniques, CILs are required to be air stable and allow uniform film formation from solvents that are immiscible with that of the photoactive layers. [10,[14][15][16] However, critical challenges persist regarding the synthesis and processing of suitable CILs that can be applied to upscaled devices and modules. Amino-containing conjugated polymers such as polyethyleneimine ethoxylated (PEIE) and polyfluorene (PFN and PFN-Br) have been adopted as CILs to deliver high-performance OPVs due to suitable film formation from solvents immiscible with photoactive layers (e.g., water and alcohols) and an ability to facilitate electron transfer to electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8,13 ] For large‐area applications that are compatible with roll‐to‐roll fabrication techniques, CILs are required to be air stable and allow uniform film formation from solvents that are immiscible with that of the photoactive layers. [ 10,14–16 ] However, critical challenges persist regarding the synthesis and processing of suitable CILs that can be applied to upscaled devices and modules.…”
Section: Introductionmentioning
confidence: 99%